Blocking of Ge/Si lattice mismatch and fabrication of high-quality SOI-based Ge film by interlayer wafer bonding with polycrystalline Ge bonding layer. (September 2022) - Ke, Shaoying; Li, Jiahui; Wang, Jie; Zhou, Jinrong; Huang, Zhiwei; Jiao, Jinlong; Ji, Ruoyun; Chen, Songyan
Abstract: We report a comparison of the Ge/SOI wafer bonding by amorphous Ge (a-Ge) and polycrystalline Ge (poly-Ge) interlayers. The Ge layer exfoliation and high-temperature annealing is used to fabricate high-quality SOI-based Ge film. The crystalline state evolution, bubble evolution, and dislocation evolution at the wafer-bonded interface are investigated. The related elimination mechanisms of bubbles and dislocations are revealed. Besides, the repairing of the point defects in the exfoliated Ge film stemmed from the H ion implantation is also demonstrated. For the a-Ge wafer bonding, when the SOI-based exfoliated Ge film is annealed at high temperature to repair the point defects, the bubbles and dislocations form at the bonded interface due to the lattice mismatch and lacking of gas transport channel ascribed to the crystallization of a-Ge (single-crystal Ge). However, for the poly-Ge wafer bonding, the poly-Ge layer not only can serve as a perfect lattice blocking layer due to its inconsistent crystal orientation, but can act as a perfect gas transporter to absorb bubbles thanks to its porous structure. The bubbles and TDs can be eliminated at high temperature during the repairing of the point defects, which in turn improves the Ge film quality. Highlights: Ge/SOI bonding with semiconductor interlayer is proposed to fabricate SOI-based Ge film. poly-Ge interlayer is an excellent gas transporter to eliminate the bubbles. The lattices of Ge/Si is isolated by poly-Ge, eliminating the dislocation nucleation. The point defects in H + -implanted Ge film are repaired after high-temperature annealing. Above three results lead to the improvement of the Ge film quality at high temperature.